Valosin-containing protein (VCP)-Adaptor Interactions are Exceptionally Dynamic and Subject to Differential Modulation by a VCP Inhibitor - Xue, Liang; Blythe, Emily E; Freiberger, Elyse C; Mamrosh, Jennifer L; Hebert, Alexander S; Reitsma, Justin M; Hess, Sonja; Coon, Joshua J; Deshaies, Raymond J (Molecular & cellular proteomics, 2016)
Protein quality control (PQC) plays an important role in stemming neurodegenerative diseases and is essential for the growth of some cancers. Valosin-containing protein (VCP)/p97 plays a pivotal role in multiple PQC pathways by interacting with numerous adaptors that link VCP to specific PQC pathways and substrates and influence the post-translational modification state of substrates. However, our poor understanding of the specificity and architecture of the adaptors, and the dynamic properties of their interactions with VCP hinders our understanding of fundamental features of PQC and how modulation of VCP activity can best be exploited therapeutically. In this study we use multiple mass spectrometry-based proteomic approaches combined with biophysical studies to characterize the interaction of adaptors with VCP. Our results reveal that most VCP-adaptor interactions are characterized by rapid dynamics that in some cases are modulated by the VCP inhibitor NMS873. These findings have significant implications for both the regulation of VCP function and the impact of VCP inhibition on different VCP-adaptor complexes.